Dynamic circulating tumor DNA indicates pathological benefits of additional neoadjuvant chemoimmunotherapy courses for locally advanced non-small-cell lung cancer patients - Lin, Dong; Wu, Liang; Wang, Pei; Li, Xiaolong; Wang, Xiaolan; Cai, Yiran; Xiong, Kangli; Chen, Xi; Yang, Fu; Huang, Wei; Wang, Xing; Fan, Jiang (Frontiers in Oncology, 2025)
IntroductionFew studies have focused on the optimal cycles of neoadjuvant chemoimmunotherapy (NCI). This study introduced minimal residual disease (MRD) based on circulating tumor DNA (ctDNA), and investigated the association between ctDNA-MRD and NCI cycles and pathological response.Materials and methodsThis study was based on a phase III trial (NCT05157776). The patients with IIIA NSCLC without driver genes were given two cycles of NCI (initial two-cycle NCI), after which they were 1:1 randomly assigned to the two-cycle NCI groups (no additional NCI) or four-cycle NCI group (with another two cycles of NCI).ResultsThis study involved 13 patients with 28 blood samples. At the start of the study, ctDNA-MRD was detected in 10 out of the 13 patients (77%). The pathologically complete response (pCR) rate was higher in the four-cycle NCI group (3/6, 50%) than in the two-cycle NCI group (1/7, 14.2%). Remarkably, the subgroup that achieved ctDNA-MRD elimination after two cycles and kept elimination after additional two cycles had the highest pCR rate (3/4, 75.0%). Correspondently, the subgroup that did not achieve ctDNA-MRD elimination after two cycles and kept existence after additional two cycles had the lowest pCR rate (0/2, 0%). Generally, in the four-cycle group, a strong correlation between ctDNA-MRD and radiological assessment was observed (5/6, 83.3%).ConclusionPatients with locally advanced NSCLC who achieved ctDNA-MRD elimination after two-cycle NCI were more likely to benefit from additional two-cycle NCI, manifesting higher pCR rates. ctDNA-MRD could be a promising tool to determine the optimal cycle of NCI.Clinical Trial RegistrationClinicaltrial.gov, NCT05157776.